Development of an Audit Procedure to Diagnose the MOP Flotation Circuit at SQM Chile - Maria Virginia Ramírez A.; Carlos F. Perucca (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
"Chile based SQM S.A., exploits potassium chloride rich salts at the Salar de Atacama, in northern Chile. The process includes the solar evaporation of natural brines existing in the Salar salt bed, followed by conventional flotation to recover Muriate of Potash (MOP) for fertilizer use.This paper describes a structured method developed to aid in understanding the metallurgical response of the solar evaporated salts to conventional flotation. The method uses classical metallurgical data analysis combined with laboratory and plant-scale testing, and rudimentary mineralogical studies.As a result of the study, several changes were made to the flotation circuit which produced an operation that is much more consistent and easier to control, and has an increased recovery. An optimized circuit, currently being financially evaluated, has also been conceptually designed based on the findings of this work.INTRODUCTIONSQM S.A. is the world’s largest producer and distributor of specialty fertilizers, iodine, lithium, as well as a wide array of industrial and specialty chemicals. SQM is a public corporation whose shares are traded in the Santiago and the New York Stock Exchanges.SQM S.A. exploits the mineral rights at the Salar de Atacama in northern Chile. Its production processes involve the solar evaporation of natural brines existing in the Salar salt bed, aimed at the recovery of Potassium, Lithium and Boron compounds."